Determinants of muscle preservation in individuals with cerebral palsy across the lifespan: a narrative review of the literature. Issue 3 (2nd February 2018) - Verschuren, Olaf; Smorenburg, Ana R.P.; Luiking, Yvette; Bell, Kristie; Barber, Lee; Peterson, Mark D.
Abstract: In individuals with cerebral palsy (CP), smaller muscle and atrophy are present at young age. Many people with CP also experience a decline in gross motor function as they age, which might be explained by the loss of muscle mass. The clinical observation of muscle wasting has prompted a comparison with sarcopenia in older adults, and the term accelerated musculoskeletal ageing is often used to describe the hallmark phenotype of CP through the lifespan. However, there has been very little research emphasis on the natural history of ageing with CP and even less with respect to the determinants or prevention of muscle loss with CP. Considering the burgeoning interest in the science of muscle preservation, this paper aims to (i) describe the characteristics of accelerated musculoskeletal ageing in people with CP, (ii) describe the pathophysiology of sarcopenia and parallels with CP, and (iii) discuss possible therapeutic approaches, based on established approaches for sarcopenia.